2018
DOI: 10.1080/13813455.2018.1484770
|View full text |Cite
|
Sign up to set email alerts
|

Swim training affects bone canonical Wnt pathway in type 2 diabetes induced by high fat diet and low dose of streptozotocin in male rats

Abstract: Swim training could partially compensate the diabetes-associated changes of Wnt pathway possibly by moderating sclerostin or blood sugar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We also found that MF treatment suppressed IL-6 release as well as NF-κB expression in the diabetic rats. Pezhman et al demonstrated that diabetes may affect bone remodeling and increase bone loss through increased RANKL/OPG ratio (Pezhman et al, 2018 ). Additionally, the decreased serum IGF-1 level in diabetic patients may contribute to the development of osteopenia (Teppala and Shankar, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that MF treatment suppressed IL-6 release as well as NF-κB expression in the diabetic rats. Pezhman et al demonstrated that diabetes may affect bone remodeling and increase bone loss through increased RANKL/OPG ratio (Pezhman et al, 2018 ). Additionally, the decreased serum IGF-1 level in diabetic patients may contribute to the development of osteopenia (Teppala and Shankar, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the most commonly used animal models, data collection on rats and mice benefit from their short gestation periods and numerous off-spring. A number of modalities of exercise training such as treadmill running, voluntary wheel running, and swim training have been utilized on rat and mice models of various genetic backgrounds [9,4548].…”
Section: Principle Of Animal Exercise Training Protocols and Sample Cmentioning
confidence: 99%
“…Swimming also caused a significant increase in BW and in RUNX2 mRNA expression, while the trabecular morphological structure of the distal femur and the indexes of bone histomorphology were not significantly improved in T2DM mice (30). Swim training significantly increased the RANKL/OPG ratio compared to the diabetic group (53,54). Based on analysis of the literature and the results of this experiment, swim training may promote the expression of early osteogenic differentiation factors, but the reduction of gravity stimulation will significantly promote bone absorption, which will lead to the reduction of bone mass.…”
Section: Discussionmentioning
confidence: 91%